Considering the bonding shear strength and flexural performance of bamboo scrimber bonded with magnesium oxysulfates adhesives of different properties - Ximing Liu; Lianfang Qiu; Xuemei Chen; Jingfan Ma (Scientific Reports)
Abstract To investigate the effects of magnesium oxysulfates adhesives with varying performance characteristics on the shear strength and bending resistance of bonded bamboo, eight types of these adhesives were prepared and applied to bamboo specimens of size 2150 mm × 22 mm × 5.5 mm for testing. The flowability, flexural strength, and compressive strength of the adhesives were measured to analyze their impact on the performance of bonded bamboo. The experimental results showed that the magnesium oxysulfates adhesive with the number H exhibited the highest adhesive shear strength under 7-day and 28 day curing conditions, at 1.05 MPa and 1.46 MPa, respectively, while the adhesive with the numbers B and A had lower strength. Magnesium oxysulfates adhesives with varying performance characteristics also had a significant impact on the bending resistance of glued bamboo. The adhesive with the number H showed the highest bending strength at 79.02 MPa under 28 day curing conditions, while the adhesive with the number B had the lowest bending strength at 39.96 MPa. The study also found that the thickness of bamboo curtains had a relatively small effect on the bending resistance of magnesium oxysulfates cementitious materials, but temperature and water immersion conditions had significant impacts on the mechanical properties of magnesium oxysulfates adhesives. After treatment at 250 °C, the peak load of magnesium oxysulfates adhesive significantly decreased, showing more pronounced performance degradation. After one year of immersion in clean water, the bending strength of magnesium oxysulfates adhesive decreased from 69 to 58 MPa, and the softening coefficient decreased from 1.0 to 0.79. From this, magnesium oxysulfates adhesivess with varying performance characteristics have significant impacts on the adhesive shear strength and bending resistance of glued bamboo. By optimizing the formula and process of magnesium oxysulfates adhesive, its application performance in glued bamboo can be significantly improved, providing scientific basis and technical support for promoting the widespread application of bamboo in construction and engineering fields.